Red flags to suspect inborn errors of immunity in patients with autoimmune diseases - Natalia Vélez; Juliette De Ávila; Jaime Cortés; Nelson Barrero; Leosirlay Rojas; Juan Manuel Bello; Consuelo Romero-Sánchez (Biomédica: revista del Instituto Nacional de Salud)
Inborn errors of immunity are monogenic disorders that predispose patients to immune dysregulation, autoimmunity, and infection. Some autoimmune diseases, such as autoimmune cytopenias, systemic lupus erythematosus, and inflammatory bowel diseases, are increasingly recognized as phenotypes of inborn errors of immunity. The objective of this article was to identify red flags or clinical/laboratory markers to suspect inborn errors of immunity in patients with autoimmune cytopenias, systemic lupus erythematosus, and inflammatory bowel diseases through a systematic literature review. The study followed the systematic reviews and meta-analysis guidelines (PRISMA). After selection, we included 36 articles, and their methodological quality was verified using the Joanna Briggs Institute tools for individual risk of bias analysis. The principal red flags in autoimmune cytopenias are chronic, recurrent, and refractory cytopenias, recurrent infection, severe infectious complications associated with immunosuppressive treatment, and chronic lymphoproliferation. In systemic lupus erythematosus, red flags include age of onset before five years, severe organ involvement, chilblain lesions, and chronic lymphoproliferation. For inflammatory bowel diseases, red flags are an age of onset before two years, resistance to conventional therapies, atypical endoscopic or histologic findings, and consanguineous parents. Autoimmune diseases may be the primary manifestation of inborn errors of immunity in pediatric and adult patients. An early diagnosis of a monogenic disorder allows for the tailoring of effective treatment plans, providing prognostic information to families, and offering genetic counseling.